Biomass Template Derived Boron/Oxygen Co‐Doped Carbon Particles as Advanced Anodes for Potassium‐Ion Batteries. Issue 1 (28th March 2021) - Lian, Xueyu; Sun, Zhongti; Mei, Qingqing; Yi, Yuyang; Zhou, Junhua; Rümmeli, Mark H.; Sun, Jingyu
Abstract : Among various anode candidates for potassium‐ion batteries, carbonaceous materials have attracted significant attention due to their overwhelming advantages including cost‐effectiveness and environmental benignity. However, the inferior specific capacity and the sluggish reaction kinetics hinder the further development in this realm. Herein, we report biomass templated synthesis of boron/oxygen heteroatom co‐doped carbon particles (BO‐CPs) via direct plasma‐enhanced chemical vapor deposition. With the combined advantages of abundant active sites, large accessible surface area, and functional groups, BO‐CP anode exhibits high reversible specific capacity (426.5 mAh g −1 at 0.1 A g −1 ) and excellent rate performance (166.5 mAh g −1 at 5 A g −1 ). The K‐ion storage mechanism is probed by operando Raman spectroscopy, ex situ X‐ray photoelectron spectroscopy/electrochemical impedance spectroscopy, galvanostatic intermittent titration technique measurements, and theoretical simulations. The synergistic effect of boron and oxygen co‐doping greatly facilitates the performance of carbon‐based anode, wherein boron dopant improves the conductivity of carbon framework and the oxygen dopant affords ample active sites and thus harvests additional specific capacity. This work is anticipated to propel the development of high‐performance anode materials for emerging energy storage devices. Abstract : Biomass templated synthesis of boron/oxygen heteroatom co‐doped carbon particles (BO‐CPs) via direct plasma‐enhanced chemical vapor deposition is realized. In terms of potassium ion storage, BO‐CP anode exhibits high reversible specific capacity (426.5 mAh g −1 at 0.1 A g −1 ) and excellent rate performance (166.5 mAh g −1 at 5 A g −1 ).